Investigating Effects of Clay and Carbonaceous Nanoparticles on Asphalt Degradation Aerobic Microorganisms - Ziari, Hassan; Goudarzi, Amir Mohammad; Goudarzi, Hossein (Novelty in Biomedicine, 2019)
Background: Hot mix asphalt (HMA) is one of the most important structures to implement the road and street surfaces, which always exposed to destruction. Provide new solutions to reduce the destructive process of effective factors on asphalt destruction and increasing prolong of its lifetime is important for society of road engineers. Traffic loading and weather conditions are the major factors that have role on different asphalt destruction. Materials and Methods: In this study, three types of HMAs, which contain nanoclay, and carbon nanotubes were produced by Marshall method in Iran University of Science and Technology, and one type of aged HMA were also collected for further investigations. The HMA samples were transferred to microbiology laboratory of Shahid Beheshti University of Medical Sciences, and then suspensions were prepared from specimens and cultured on nutrient agar medium. After 24 hours’ incubation at 37 ̊C the bacteria that were grown on the plate were identified. At least the effect of clay and carbon nanoparticles on minimum inhibitory concentration (MIC) of bacteria, were determined by microdilution broth method. Results: A lot of bacterial colonies (Bacillus and Pseudomonas) were collected from the aged specimens. The asphalt, which contain nanoclay had more bacteria than the nanocarbon asphalt. The carbon and clay nanoparticles in 2% and 4% concentration prevented the growth of bacteria, respectively. Conclusion: The old asphalt had more bacteria than other samples, which shows bacteria are one of the main factors in decomposition of asphalt by applying corrosion to bituminous hydrocarbons. Presence of clay and carbon nanoparticles in asphalt structures could increase the durability of the HMAs and reduce the relevant economics costs.